Advances in hepatitis E – I: virology, pathogenesis and diagnosis. (1st September 2016) - Aggarwal, Rakesh; Goel, Amit
ABSTRACT: Introduction : Infection with hepatitis E virus (HEV) is the commonest cause of acute hepatitis worldwide. HEV was discovered in 1980s and is known to have small non-enveloped virions with single-stranded RNA genome of positive polarity. In recent years. In recent years, availability of new information has changed our understanding of this virus and the pathogenesis of the related disease. Areas covered : This article reviews the current knowledge about structure, genomic organization, taxonomy, genetic epidemiology, host specificity and replication of the human HEV and of various closely-related viruses that infect other animals. In addition, the models available for the study of HEV infection, the available information on the pathogenesis of this infection and the techniques available for its diagnosis are also reviewed. Expert commentary : A circulating, enveloped form of the human HEV has been recently recognized. Originally believed to naturally infect only humans and possibly primates, HEV-like viruses are now known to infect several vertebrate animals. Based on this, phylogenetic classification of these viruses has recently been revised. In vitro replicons and infection systems have been developed, which have improved our understanding about the virus and the pathogenesis of infection with it. Recent development of mouse models with chimeric livers that contain human hepatocytes provides another avenue for further advancement of this knowledge.